CIVILIZATIONAL AND HISTORICAL ANTHROPOLOGY ASPECTS OF THE «GREEK MIRACLE» - Spartak Sh. Aytov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the work is to study the impact of geographical, social and cultural context, mentality character-istics of historical process of society on the origin and characteristics of the development of intellectual achieve-ment, namely philosophy and science. The purpose of the article is to understand natural, historical, cultural, social and psychological aspects that led to the genesis of cognitive development peculiarities of ancient Greek philosophy of scientific knowledge. Methodology. Methodology of the work contains such cognitive approaches as systematic and structural ones, source study and post-positivist concepts, the theory of local civilizations. Theoretical basis and results: the novelty of this work is in studying the diverse factors that determined the emergence and dynamics of ancient Greek philosophical thought and science as a whole system of interrelated elements. The influence on the genesis of philosophy and science of ancient Hellas, its geographical conditions and geopolitical situation as well as the cultural dialogue with surrounding civilizations, the reception of historical and cultural experience of the previ-ous Hellenic civilization, historical process and mentality of ancient Greeks have been analyzed. Conclusions: the whole cluster of the above mentioned factors had a profound and multi-directional influence on the formation and development of Greek philosophy and science. In addition, each of the factors influenced the original intellectual achievements of Greeks. In particular, the influence of natural factors realized in the formation of skills in the men-tality of ancient Greeks has become a prerequisite for philosophizing and scientific knowledge. Geo-political, social and cultural factors have contributed to the geographical expansion of ancient Greeks and their information acquisi-tion about the world. Through the dialogue with other eastern and Mediterranean cultures Greeks mastered intellec-tually rich and meaningful experience of a number of great civilizations. The precursor forms of intellectual activity have played a significant role in the genesis of ancient Greek philosophy and science. Synergy interaction of these factors has led to rapid development of philosophy and science of ancient Hellas.